The war with Grandpa [videorecording (DVD)] - De Niro, Robert; Thurman, Uma; Riggle, Rob; Fegley, Oakes; Marin, Cheech; Seymour, Jane, 1951-; Walken, Christopher, 1943-; Smith, Robert Kimmel, 1930-2020 (Universal Pictures Home Entertainment, 2020)
Sixth grader Peter is pretty much the average kid: he likes gaming, hanging with his friends, and his beloved pair of Air Jordans. But when he has to give up his most prized possession -- his bedroom -- when his recently widowed grandfather moves in with Peter's family, he's unwilling to let such an injustice stand. Peter devises a series of increasingly elaborate pranks to drive out the interloper, but Grandpa Ed won't go without a fight.